Roy Wilkins : the right to dignity - United States. International Communication Agency (Washington : The Agency : distributed by National Audiovisual Center, 1978)
Reviews the career of Black activist Roy Wilkins with the National Association for the Advancement of Colored People. Outlines the growth and impact of the organization, including its role in the 1954 Supreme Court ruling on school desegregation and the landmark civil rights legislation of the 1960's.
Title from data sheet.
U standard.
Also issued as motion picture.
Narrator, Sidney Poitier.
Keywords: Wilkins, Roy, -- 1901-; National Association for the Advancement of Colored People; African Americans -- Civil rights; African Americans -- Biography